1999
DOI: 10.2190/afdd-k6qc-6m1u-mve4
|View full text |Cite
|
Sign up to set email alerts
|

The Grief of Sids Parents and their Understanding of Each Other's Responses

Abstract: This article reports on a survey of sixty-one parents (including 27 couples) who had recently experienced the loss of an infant to Sudden Infant Death Syndrome (SIDS). Data were collected on parents' reactions to the death, things which helped with grief, sources of solace, and attitudes to another pregnancy. Some sets of questions were presented twice: in the f m t instance the respondent reported hisher own situation and in the second instance the respondent estimated hisher partner's situation. In some area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…There is not adequate support around paternal leave, and pregnancy loss is often not perceived as a death. Returning to work as an escape was acknowledged by three fathers in this study, a finding seen by others (Irizarry & Willard, 1999). While work may be a convenient escape from dealing with feelings, work also robs time needed for processing and, fathers, just like mothers, need time to heal.…”
Section: Discussion and Implications For Caresupporting
confidence: 77%
See 2 more Smart Citations
“…There is not adequate support around paternal leave, and pregnancy loss is often not perceived as a death. Returning to work as an escape was acknowledged by three fathers in this study, a finding seen by others (Irizarry & Willard, 1999). While work may be a convenient escape from dealing with feelings, work also robs time needed for processing and, fathers, just like mothers, need time to heal.…”
Section: Discussion and Implications For Caresupporting
confidence: 77%
“…Higher grief scores for men years after a loss may be due to their need to stay in control and be problem focused, assuming the protector role for the woman ( DeFrain, 1991;Doka & Martin, 2001;Long, 1992;Samuelsson et al 2001;Worth, 1997 ). Fathers whose partners experienced a miscarriage expressed feelings of helplessness and lack of control, saw their primary role as support for their partner, and held back their own feelings to do this ( Irizarry & Willard, 1999;McCreight, 2004;Miron & Chapman, 1994;Murphy, 1998 ). The protector role may tone down emotional response in general, leading to a sense of failure and feelings of guilt, especially if the deceased was one of the " protected " Levang, 1998 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carroll and Schaefer (1994) found that bereaved mothers were more likely than fathers to seek support both outside and within the family, including crying with friends and asking for prayer, holding their partner or spouse, and accepting support from their partners or spouses. These findings, generally supporting higher levels of affective response, distress, and support seeking in mothers than in fathers, were corroborated in similar studies by Irizarry and Willard (1998) and Kavanaugh (1997). Research on other populations, including middleaged adults reacting to the death of a parent (Douglas, 1990;Moss, Resch, & Moss, 1997) and adolescents responding to the death of a parent (Lenhardt & McCourt, 2000;Meshot & Leitner, 1993); Recklitis & Noam, 1999) have demonstrated similar findings.…”
Section: Introductionsupporting
confidence: 61%
“…As can be seen from Table 1, the review of the literature reveals that six ad hoc questionnaires have been used in quantitative studies (Williams and Nikolaisen, 1982;Price et al, 1985;Dyregrov and Matthiesen, 1987;Thuen, 1997;Irizarry and Willard, 1999;Goldstein et al, 2020). Of these six studies, three also used other instruments, such as the Impact of Event Scale (IES), the 20-item Goldberg General Health Questionnaire (GHQ-20), the State-Trait Anxiety Inventory (STAI), the Bodily Symptom Scale (BSS), the Beck Depression Inventory Short Form (BDI-SF) (Dyregrov and Matthiesen, 1987), the Symptom ChackList-90 and Bradburn's Affect-Balance Scale (Thuen, 1997), and the Parental Bereavement Questionnaire (PBQ) (Goldstein et al, 2020).…”
Section: Data Extractionsmentioning
confidence: 99%